2020
DOI: 10.1016/j.comcom.2020.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Towards a distributed and infrastructure-less vehicular traffic management system

Abstract: In the past few years, several systems have been proposed to deal with issues related to the vehicular traffic management. Usually, their solutions include the integration of computational technologies such as vehicular networks, central servers, and roadside units. Most systems use a hybrid approach, which means they still need a central entity (central server or roadside unit) and Internet connection to find out an en-route event as well as alternative routes for vehicles. It is easy to understand the need f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 25 publications
0
13
0
1
Order By: Relevance
“…The aim of this type of interaction is largely to make it possible for safety and security applications like staying clear of automobile accidents as a result of various reasons like roadway problems, climate condition, roadside building or malfunctioning traffic control. This technology alerts the motorist about accidents, traffic, sharp contours, and with suggested speeds [46,47].…”
Section: B) Vehicle To Infrastructurementioning
confidence: 99%
“…The aim of this type of interaction is largely to make it possible for safety and security applications like staying clear of automobile accidents as a result of various reasons like roadway problems, climate condition, roadside building or malfunctioning traffic control. This technology alerts the motorist about accidents, traffic, sharp contours, and with suggested speeds [46,47].…”
Section: B) Vehicle To Infrastructurementioning
confidence: 99%
“…Most of these techniques consider the speed-based lane change model to reduce traffic congestion which will result in fewer road accidents due to improper lane change. A vehicle traffic management system (dEASY) is proposed in [128] to deal with traffic events that may have an impact on the overall network performance. This system considers three different layers to implement an architecture that is capable to deal with the selection of the best vehicle to forward data by implementing an altruistic approach to choose alternative routes.…”
Section: Traffic Optimization In Vehicular Networkmentioning
confidence: 99%
“…More and more vehicles are being equipped with devices that can provide numerous services and applications for managing street traffic or even the entire traffic system in a large city [2]. Because of that, the Intelligent Transport Systems (ITSs) are envisioned to provide a number of new applications that spread from road and traffic alerts [3][4][5], distributed and cooperative route planning [6][7][8][9][10], several types of video distribution [11][12][13][14][15], driving strategy advisory systems [16][17][18], to autonomous driving capabilities [19][20][21]. A report conducted by the Institute of Economic and Applied Research showed that more than 169,000 traffic accidents were registered on the federal highways in Brazil in 2014 [22].…”
Section: Introductionmentioning
confidence: 99%